Fall Seven Times, Stand Up Eight: Linking Project Management Innovation, Project Governance, and High-Performance Work Practices to Project Success - Zaman, Umer; Khan, Mohammad Nasar; Raza, Syed Hassan; Farías, Pablo (Frontiers in Psychology, 2022)
Project managers seem to be puzzled in resolving the global dilemma of project failures across industries. Hence, the present study introduces project management innovation (PMI) as a determinant of project success (PS) and explores whether project governance (PG) and high-performance work practices (HPWPs), strengthen this relationship. To confirm these propositions, study data using adapted scales were collected from project professionals representing software development companies in the emerging IT industry in Pakistan. Structural equation modeling (SEM) was employed to examine the hypothesized relationships and encourage PMI guided solutions for project failures. SEM results statistically validated that project success is positively influenced by PMI, whereas this relationship is significantly strengthened through the moderating influence of PG and HPWPs, respectively. Theoretically, the present research is the first of its kind to introduce and empirically examine these untested relationships between PMI, PG, HPWPs and PS in a single framework. These novel findings hold strategic value for both project managers and organizational leaders who oversee a range of project portfolios. Long-lasting advantages and superior achievements can be reinvigorated through PMI, after departure from traditional approaches and answering calls for new solutions to new problems in managing projects. Moreover, project governance and HPWPs should be reconfigured to oversee, as well as meet the special needs of each unique project.